2010
DOI: 10.1007/s10995-010-0648-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Family-Centered Care with Health Care Outcomes for Children with Special Health Care Needs

Abstract: The objective of this study is to examine the association of family-centered care (FCC) with specific health care service outcomes for children with special health care needs (CSHCN). The study is a secondary analysis of the 2005-2006 National Survey of Children with Special Health Care Needs. Receipt of FCC was determined by five questions regarding how well health care providers addressed family concerns in the prior 12 months. We measured family burden by reports of delayed health care, unmet need, financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
103
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 41 publications
10
103
1
7
Order By: Relevance
“…Hence, it is important that such type of care be inserted into healthcare policies, aiming at both integrating the care services in all healthcare levels, (11) and improving the quality of life of the families and their children.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important that such type of care be inserted into healthcare policies, aiming at both integrating the care services in all healthcare levels, (11) and improving the quality of life of the families and their children.…”
Section: Discussionmentioning
confidence: 99%
“…18 It has also been reported that children with special health care needs experienced significantly fewer adverse family financial and economic impacts if the affected child has a medical home or a family-centered system of health care. 13,19 Similarly, children with special health care needs who had access to family-centered care in a medical home and had adequate health insurance scored higher on a latent-variable well-being construct that was strongly predictive of family financial problems and negative financial impact. 20 This study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A investigação empírica tem comprovado que esta abordagem traz importantes benefícios para a adaptação psicológica das crianças (Kuo, Bird, & Tilford, 2011;Stein & Jessop, 1984), bem como dos pais, nomeadamente a redução do sofrimento emocional e da sintomatologia depressiva (King, King, Rosenbaum, & Goffin, 1999;Stein & Jessop, 1984) e ansiosa (Ireys, Chernoff, DeVet, & Kim, 2001;Stein & Jessop, 1984). Esta abordagem parece ainda promover a satisfação com os cuidados de saúde formais (King et al, 1999) e a redução dos níveis de sobrecarga dos cuidadores familiares (Kuo et al, 2011).…”
Section: Os Cuidados Centrados Na Família Nas Unidades Pediátricasunclassified
“…Esta abordagem parece ainda promover a satisfação com os cuidados de saúde formais (King et al, 1999) e a redução dos níveis de sobrecarga dos cuidadores familiares (Kuo et al, 2011). Também no contexto da oncologia pediátrica, existe evidência de que os CCF se associam a uma melhor qualidade de vida das crianças ) e dos A maioria dos estudos no âmbito dos CCF tem focado o seu impacto psicossocial em pais e crianças (Harrison, 2010).…”
Section: Os Cuidados Centrados Na Família Nas Unidades Pediátricasunclassified
See 1 more Smart Citation